IMPLICAŢIILE RELIEFULUI ÎN DEZVOLTAREA ŞI ESTETICA URBANĂ A SIBIULUI (PANGEEA, 2025)
Sibiu is one of the most important city from Transilvania . Is located on many kinds of relief that demanded on upgrade of teren constructions . The city was guided by relief geometrical forms ro tahe over space, with stability and nonstabitity geomorphological and the development of the slopes.